The Effectiveness of Financial Literacy Education on Children's Economic Decision-Making: A Meta-Analysis Approach - Hatidja, ST.; Suhardi, Suhardi; Fauzi, Rizal Ula Ananra; Hudaeni, Nurul; Oktora, Ria; Afrizal, Afrizal; Santosa, Tomi Apra; Yastanti, Unpris (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2025)
This study aims to determine the influence of financial literacy education on children's economic decision-making. This type of research is quantitative research with a meta-analysis approach. The inclusion criteria in this study are 1) data from national and international journals indexed by SINTA and Scopus, 2) research published in 2021-2024, 3) research must be relevant, 4) research data must report complete data to calculate the effect size value. Research data was obtained from 25 studies that have met the inclusion criteria—data analysis with the help of the JASP 0.8.5 application. The study's results concluded that the average effect size value was ( d = 0.994; z = 11.198; p< 0.001) in the high effect size category. These findings show that financial literacy education significantly influences children's decision-making.